Fostering motivation to learn islamic cultural history through the role-playing method - Zubaidi, Ahmad; Yakin, M. Fajri Ainul (LP3M Universitas Islam Zainul Hasan Genggong, 2025)
This study aims to analyze the application of the role-playing method in enhancing students' learning motivation in the subject of Islamic Cultural History at MTs Darul Hikmah, Paiton, Probolinggo. Learning motivation is a critical factor influencing the success of education, especially in subjects requiring an understanding of history and culture. The role-playing method was chosen because it provides an interactive learning experience, allowing students to delve deeper into the material through role simulation. This research employs a qualitative approach with a classroom action research (CAR) method. The research subjects consisted of 30 eighth-grade students at MTs Darul Hikmah. These students were selected as they represent a diverse group with varying levels of learning motivation and understanding of Islamic Cultural History. Data were collected through observation, interviews, questionnaires, and documentation. The findings indicate that the implementation of the role-playing method significantly improved students' learning motivation. This was evident from students' active participation during lessons, improved comprehension of the material, and their enthusiasm in performing assigned roles. Additionally, the method encouraged good collaboration and communication among students. The conclusion of this study is that the role-playing method is effective in enhancing motivation to learn Islamic Cultural History. Therefore, this method is recommended for broader application by educators, particularly in subjects requiring conceptual and contextual understanding.